P‐11: Development of IGZO ESL Type TFTs at G8.5 for 55" AMOLED TVs. Issue 1 (May 2016) - Wang, Dongfang; Yuan, Guangcai; Zhao, Ce; Zhou, Bin; Liu, Guanghui; Ding, Luke; Wang, Ming; Cheng, Jun; Liu, Jun
Abstract : The ESL type IGZO oxide semiconductor TFTs with high Vth uniformity of delta Vth less than 1V, and high reliability has been developed at BOE G8.5 for 55inch AMOLED TVs. The mobility was ~10 cm2/Vs, the threshold voltage (Vth) shifts of BTS were successfully reduced to less than 1V and the Vth shifts of hysteresis were less than 0.1V. Furthermore, 55inch AMOLED TVs based on ESL type IGZO TFTs were produced with external compensation circuits.